2011
DOI: 10.3109/02713683.2011.574332
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Transparency of the Rabbit Cornea Irradiated with UVB-Doses of 0.25 J/cm2and 0.5 J/cm2Compared with Equivalent UVB Radiation Exposure Reaching the Human Cornea from Sunlight

Abstract: Changes in corneal hydration appeared after the exposure of the rabbit cornea to a single UVB dose equivalent to 2.6 hours of solar UVB radiation reaching the human cornea, as measured by UVB sensors embedded in the eyes of mannequin heads facing the sun on a beach at noon in July. Repeated exposure of the rabbit cornea to the same UVB dose evoked profound changes in corneal optics. Although comparison of experimental and outdoor conditions are only approximate, the results in rabbits point to the danger for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The technique was reported for rabbits in the 1950s (24) and provides an objective assessment of any compromise of the cornea since this will be expected to result in an increase in corneal thickness. Pachymetry is the logically preferred method for objective assessment of UV-B-induced cornea edema (rather than simply assigning a grade) and has been used in numerous rabbit studies to assess the effects of UV-B exposure (8,15,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The assessments of corneal thickness do not need to be made by optical pachymetry on the living eye for an alternative is to use an ultrasound pachymeter.…”
Section: Specialized In Vivo or Ex Vivo Assessments Of The Rabbit Cormentioning
confidence: 99%
See 2 more Smart Citations
“…The technique was reported for rabbits in the 1950s (24) and provides an objective assessment of any compromise of the cornea since this will be expected to result in an increase in corneal thickness. Pachymetry is the logically preferred method for objective assessment of UV-B-induced cornea edema (rather than simply assigning a grade) and has been used in numerous rabbit studies to assess the effects of UV-B exposure (8,15,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The assessments of corneal thickness do not need to be made by optical pachymetry on the living eye for an alternative is to use an ultrasound pachymeter.…”
Section: Specialized In Vivo or Ex Vivo Assessments Of The Rabbit Cormentioning
confidence: 99%
“…c) of the enucleated eye . The ultrasound pachymeter is especially useful when even 2× fold increases in corneal thickness develop after repeated exposure to high doses of UV‐B irradiation .…”
Section: Specialized In Vivo or Ex Vivo Assessments Of The Rabbit Cormentioning
confidence: 99%
See 1 more Smart Citation
“…And there was a relative association between pterygium, sun exposure, and serum 25-hydroxyvitamin [10]. Furthermore, a study found that repeated exposure of the rabbit cornea to the same UVB irradiation evoked profound changes in corneal optics [11]. However, there was a lack of detailed information of UVB-induced damage on infancy cornea and relative protective measures.…”
Section: Introductionmentioning
confidence: 99%
“…According to Čejka et al (2011), 1.1 J/cm 2 of UV‐B radiation from sunlight reaches earth per hour at 40°N latitude at noon in July. Taking into consideration the data in the literature, the transmission of UV‐B radiation though human skin ranges from approximately 1 to 10%, depending on different skin sites and methods of measurements (Hoffmann et al, 2000; Meinhardt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%